A novel role of centrin in flagellar motility: stabilizing an inner-arm dynein motor in the flagellar axoneme - Ziyin Li (Microbial Cell)
Centrin is an evolutionarily conserved EF-hand calcium-binding protein found in the centriole of animals and the basal body of flagellated organisms. It was originally discovered in the flagellated unicellular green alga Chlamydomonas reinhardtii, where it associates with flagellum-associated structures and regulates basal body duplication and flagellar motility. Centrin constitutes a light chain of three inner-arm dynein complexes in the flagellar axoneme in Chlamydomonas, and presumably regulates the activity of the inner-arm dynein for flagellar motility. In the ciliated organism Tetrahymena, centrin also associates with the inner-arm dynein and appears to regulate the microtubule sliding velocity of the inner-arm dynein. Using Trypanosoma brucei as the model organism, we discovered that centrin maintains the stability of an inner-arm dynein in the flagellar axoneme [Wei et al., (2014) Nat. Commun 5: 4060]. T. brucei expresses five centrins, three of which, TbCentrin1, 2, and 4, associate with the flagellar basal body, but no centrin was found to regulate cell motility. We found that TbCentrin3 associates tightly with the flagellum and that RNAi of TbCentrin3 compromised cell motility. Biochemical approaches further showed that TbCentrin3 interacts with TbIAD5-1, an inner-arm dynein in the flagellar axoneme. Knockdown of TbIAD5-1 also caused defective cell motility. Strikingly, depletion of TbCentrin3 or depletion of TbIAD5-1 resulted in disassembly of the complex from the axoneme and subsequent degradation of the complex in the cytosol. Our findings identified a novel role of TbCentrin3 in cell motility by stabilizing TbIAD5-1 in the axoneme, which likely is well conserved in other flagellated and ciliated organisms, such as Chlamydomonas and Tetrahymena where centrin is also known to associate with inner-arm dyneins.